Analisis Pengelolaan Arsip Konvensional pada Divisi Administrasi Keuangan di PT Berlian Laju Tanker Tbk - Yashi Nicafisa Riventa Br Ginting; Dewi Nurmalasari; Suherdi Suherdi (Indo Publishing, 2026)
This study aims to analyze the conventional archive management system in the Financial Administration Division at PT Berlian Laju Tanker Tbk, including the storage system, challenges faced, and efforts to improve security. This study employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation involving four informants from the Finance Division. The results indicate that the conventional archive management system is still actively used alongside the digital system, as physical documents such as transaction evidence, payment vouchers, and financial reports are considered to have high authenticity value. The manual storage system using filing cabinets with classification based on transaction type and time period reflects the implementation of chronological and subject-based storage systems. The main challenges include limited storage space due to the increasing volume of documents without periodic disposal, leading to accumulation that reduces document retrieval efficiency and increases the risk of physical damage to archives. Efforts to improve security include strengthening physical management through systematic arrangement and digitalization through document scanning as a backup. The implementation of a dual storage system (physical and digital) is considered capable of enhancing information security and accelerating document retrieval. The findings of this study confirm that the combination of well-organized physical archive management and the utilization of digital technology is an effective strategy in maintaining the security and sustainability of archives.